The Role of Innovation in Development of Islamic Financial Products in Makassar - Muhammad Agung Miftah Syamsul Alam; Adi Muh Arman; Lince Bulutoding (GoodWill, 2026)
This research aims to explore the role of innovation in the development of Islamic financial products in Makassar, focusing on the challenges and opportunities involved. The research methodology includes in-depth interviews, participatory observation, and documentary analysis to gain a profound understanding of the perception and implementation of innovation among Islamic banks, regulators, and the Makassar community. The findings indicate that despite efforts to introduce new products and improve services, Islamic banks in Makassar still face challenges regarding public understanding of Islamic financial products and the need for further refinement of regulations. However, there are significant opportunities through the integration of financial technology (fintech) to enhance access and efficiency of Islamic financial services. The study concludes that closer collaboration among Islamic banks, government authorities, and educational institutions is necessary to enhance Islamic financial literacy and develop regulations that support sustainable innovation. The practical implications of these findings include the development of effective communication strategies and comprehensive education programs to expand the user base of Islamic financial products in Makassar. This research provides a significant contribution to understanding how innovation can play a crucial role in developing an inclusive and sustainable Islamic financial ecosystem in the city of Makassar, Indonesia.